Wpływ środków masowego przekazu na sympatie polityczne studentów – analiza wyników badań własnych - Pawełczyk, Piotr; Jankowiak, Barbara (Wydawnictwo Naukowe UAM, 2012)
The article contains an evaluation of results of a survey carried out among Poznań university students. Its purpose was to investigate which media are used by students in order to obtain socio-political information and what kind of attitudes towards political parties and politicians are connected to the use of certain mass media. In today’s democracy media play the role which is hard to overestimate but crucial changes occur as to their potential impact on the individuals’ attitudes. The young generation of the electorate entering adult life read fewer and fewer newspapers and magazines, choosing instead the Internet rather than television. The assumption about the subjectivism of mass media content infl uencing the various emotions of audiences was almost completely confi rmed. The survey results show that the press and TV news programs are far advanced in the process of an intentional creation of images of reality. However, the increasing role of Internet portals introduces new features to public discourse, resulting in a greater balance of political attitudes
The Infl uence of Mass Media on Political Attitudes of Students vs. Analysis of Own Research
Keywords: mass media; political attitudes; affective orientation; political socialization